ANALISIS DESAIN FORMULIR KARTU PENGOBATAN PENCEGAHAN TB (TB 01 P) UNTUK KELENGKAPAN DATA DI PUSKESMAS TAHUN 2019 - Suyoko suyoko; Retno Astuti Setijaningsih; Wahyu Setiyowati (Dian Nuswantoro Semarang, 2020)
Tuberculosis is an infectious disease which becomes a global problem. The increase in TB case is caused by inadequate monitoring of treatment, unavailability of standardized recording and reporting system. This research was conducted to evaluate the completeness TB form design in providing more complete information. This research was administered in the form of a case study. Interviews were done to 3 nurses and 1 doctor and TB Form (TB.01P) was observed at Miroto Health Center. The completeness of 33 TB form filling (TB.01P) at the Malmahera Health Center was also evaluated. The obtained data were descriptively analyzed. The results showed the completeness of identification review reached 96%, recording review of 90%, reporting review of 64%,and 0% for authentication review. Incomplete information led to inaccurate TB control information. This incompleteness was associated toimproper design of the form, especially the unavailability of form filling instructions, names and signatures of officersin the anatomic aspect. In the aspect of content, lack of clinical data was also found. Regarding to the results of this research, revision in the design of TB Treatment and Prevention Card is needed in order to accommodate the data completeness of TB patients. This research also proposed a better design of TB Treatment and Prevention Card Keywords : Quantitative Completeness, Tuberculosis, Form Design, TB Treatment Card (TB.01P)